Evaluation of a treatment protocol for anaemia in pregnancy nested in routine antenatal care in a limited-resource setting - Gilder, M; Simpson, J; Bancone, G; McFarlane, L; Shah, N; Van Aalsburg, R; Paw, M; Pimanpanarak, M; Wiladphaingern, J; Myat Min, A; Turner, C; Rijken, M; et al. (Taylor and Francis, 2019)
Background: Anaemia in pregnancy is typically due to iron deficiency (IDA) but remains a complex and pervasive problem, particularly in low resource settings. At clinics on the Myanmar–Thailand border, a protocol was developed to guide treatment by health workers in antenatal care (ANC). Objective: To evaluate the clinical use of a protocol to treat anaemia in pregnancy. Methods: The design was a descriptive retrospective analysis of antenatal data obtained during the use of a standard anaemia treatment protocol. Two consecutive haematocrits (HCT) ≺30% prompted a change from routine prophylaxis to treatment doses of haematinics. Endpoints were anaemia at delivery (most recent HCT before delivery ≺30%) and timeliness of treatment initiation. Women whose HCT failed to respond to the treatment were investigated. Results: From August 2007 to July 2012, a median [IQR] of five [4–11] HCT measurements per woman resulted in the treatment of anaemia in 20.7% (2,246/10,886) of pregnancies. Anaemia at delivery was present in 22.8% (511/2,246) of treated women and 1.4% (123/8,640) who remained on prophylaxis. Human error resulted in a failure to start treatment in 97 anaemic women (4.1%, denominator 2,343 (2,246 + 97)). Fluctuation of HCT around the cut-point of 30% was the major problem with the protocol accounting for half of the cases where treatment was delayed greater than 4 weeks. Delay in treatment was associated with a 1.5 fold higher odds of anaemia at delivery (95% CI 1.18, 1.97). Conclusion: There was high compliance to the protocol by the health workers. An important outcome of this evaluation was that the clinical definition of anaemia was changed to diminish missed opportunities for initiating treatment. Reduction of anaemia in pregnancy requires early ANC attendance, prompt treatment at the first HCT <30%, and support for health workers.